Conceptual Framework of the Impact of Health Technology on Healthcare System - Farid, Samar F. (Frontiers in Pharmacology, 2019)
The World Health Organization (WHO) promotes health systems strengthening as a means of improving population health, especially in low- and middle- income countries. The United Nations Sustainable Development Goals have made apparent the importance of investing in workforce development to improve population health and economic well-being. In relation to pharmaceuticals, health systems face challenges in terms of: (i) guaranteeing access to needed drugs, (ii) rationalizing medicines use, and (iii) avoiding harm from adverse events. For medicines systems to be strengthened there is a pressing need to better understand the relationships between technology and pharmacy practice when strengthening pharmaceutical care systems. In response, this paper will examine ways in which harnessing new technologies can change pharmacy practice in ways that strengthen pharmaceutical systems for the benefit of patients. The paper will present a conceptual framework as well as exploring case studies.